Optimal Sense-Making and Resilience in Times of Pandemic: Integrating Rationality and Meaning in Psychotherapy - Russo-Netzer, Pninit; Ameli, Matti (Frontiers in Psychology, 2021)
The global COVID -19 pandemic has triggered a wide variety of psychological crises worldwide. In order to respond rapidly and efficiently to the complex challenges, mental health professionals are required to adopt a multidimensional and integrative view. Rational Emotive Behavior Therapy (REBT) founded by Albert Ellis promotes rationality and self-acceptance. Logotherapy, pioneered by Viktor Frankl potentiates meaning and resilience. Both approaches are complementary and mutually enriching. The goal of this paper is to propose an integrative model of “optimal thinking”, a concept that combines both rationality and meaning, as well as the role of self-transcendence and healthy negative emotions. The model offers a theoretical and clinical foundation for efficient and effective psychological intervention plans for those affected by the pandemic. Along with theoretical background, illustrating case studies will be presented to support potential application of the integrative model to affected individuals as well as the work of first line health professionals during these times of pandemic. Implications are considered for utilizing theoretical and applied insights from the model to cultivate resilience in face of adversity and suffering.